København : urban architecture and public spaces - Hofmeister, Sandra, ....- (Munich : Edition Detail, 2021)
This book reveals Copenhagen's quality of life using the example of built spaces. It leads its readers on a tour of exploration, visiting exciting architecture projects and surprising districts between Orestadt and Nordhavn. A total of over 25 exceptional buildings, urban squares and public spaces created in the past 10 years are presented. Documented with brilliant photos, general plans and texts, these projects paint an image of a brave generation of architects and planners who are not afraid to employ novel solutions. On display are daring typologies such as Amager Bakke, a ski slope on a waste incineration plant by BIG, spectacular iconic buildings, including the Royal Danish Aquarium by 3XN or popular public spaces for the urban community.
Keywords: Architecture; Public spaces